2006
DOI: 10.1002/bit.20762
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of protein secretion inPichia pastoris by overexpression of protein disulfide isomerase

Abstract: A potential vaccine candidate, Necator americanus secretory protein (Na-ASP1), against hookworm infections, has been expressed in Pichia pastoris. Na-ASP1, a 45 kDa protein containing 20 cysteines, was directed outside the cell by fusing the protein to the preprosequence of the alpha-mating factor of Saccharomyces cerevisiae. Most of the protein produced by single copy clones was secreted outside the cell. However, increasing gene copy number of Na-ASP1 protein in P. pastoris saturated secretory capacity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(98 citation statements)
references
References 27 publications
6
90
1
1
Order By: Relevance
“…It is reported that overexpression of protein disulfide isomerase could enhance protein secretion in Pichia pastoris (Inan et al 2006). Considerable deviations in the secondary structure of rCel7A compared to H. jecorina Cel7A, revealed by circular dichroism, were also observed in previous studies (Godbole et al 1999;Boer et al 2000).…”
Section: Discussionmentioning
confidence: 71%
“…It is reported that overexpression of protein disulfide isomerase could enhance protein secretion in Pichia pastoris (Inan et al 2006). Considerable deviations in the secondary structure of rCel7A compared to H. jecorina Cel7A, revealed by circular dichroism, were also observed in previous studies (Godbole et al 1999;Boer et al 2000).…”
Section: Discussionmentioning
confidence: 71%
“…Optimization of Heterologous Expression-To overcome the low level of expression for BBE H104A and H104A-C166A reported previously (20), we attempted to improve the level of secretory expression in Pichia pastoris by co-overexpression of protein disulfide isomerase (PDI), a protein reported to have a general positive effect on the secretory machinery in yeasts (22,23). The plasmid containing the coding sequence of PDI from P. pastoris in the vector pPICK was a generous gift of Prof. A. Glieder and Dr. S. Abad.…”
Section: Methodsmentioning
confidence: 99%
“…These auxiliary chaperones can load substrates into the HSP90 molecular chaperone [24], assist in the folding of heterologous proteins, and re-target substrates into degradable pathways [9]. Disulfide isomerase (PDI) is responsible for the catalytic acceleration of further folding of heterologous proteins [25]. PDI has two bioactivities: it acts as a disulfide bond-dependent and bond-independent molecular chaperone, and is responsible for the formation and isomerization of the disulfide bond [26].…”
Section: Endoplasmic Reticulum Resident Proteins and Their Effect On mentioning
confidence: 99%